Reestruturação produtiva e dependência econômica : agronegócio de laticínios e pequenos produtores rurais de Bela Vista de Goiás (1986-2019) - (:unkn) unknown (Universidade Estadual de Goiás, 2020)
The 1980s and 1990s sawsignificantchanges in agriculturalproduction, accompanying a processthatbegan in urban industrial productionandbecameknown as productiverestructuring. Basedon neoliberal ideology, theproductiverestructuring in thecountrysidemeantadaptingtheproductive systems tothelogic of the market, enteringwhatweknowas agribusiness, even in the case ofsmallandmedium rural producers, oftendriven / compelledbythegrowingmonopolyofproduction and trade in rural areas. Goodsproducedbycompaniesandothereconomicinstitutions, such as cooperatives. Base don’t hispremise, thisresearchseekstounderstandthe role ofone of the largestdairy industries in Brazil, Piracanjuba owner, ownerofhePiracanjuba brand, in the processo fproductiverestructuringof its supplychain, in themunicipalityof Bela Vista de Goiás. Founded in the 1980s, whilebecomingthelargestindustry in thecityof Bela Vista de Goiás andsurroundingcities, monopolizingdairyproduction, it made local dairyfarmersdependentontheirincreasinglydemandingpurchasing policy. Mechanizationofproductionandmodernizationandstandardizationof processes. In thesamevein, weseektounderstandhowman'swaysoflife in thecountrysidehavealsochanged. Methodologically, theresearchinitiallyopted for a literaturereviewonthetheme, conceptsandcategoriesused. In thefieldresearch, weopted for the case study, usingthe Oral History procedures as an approach, startingfrom interviews withpreestablishedandinductivequestionnaires, withsmallfarmersinserted in thesupplychainofthe Bela Vista Dairy, tounderstandthe Inthiswaytheyelaboratethememoryofboththedependenceandthechangesexperienced in thelastthreedecades.
Productive restructuringand economic dependence : the impactsofdairy agribusiness on the lifestyles of small rural producers in Bela Vista de Goiás (1986-2017)
Keywords: Reestruturação produtiva; Dependência econômica; Agronegócio; Modos de Vida; Productive restructuring; Economic dependence; Agribusiness; Lifestyle; OUTROS